Mitochondrial Permeability Transition Pore Sealing Agents and Antioxidants Protect Oxidative Stress and Mitochondrial Dysfunction Induced by Naproxen, Diclofenac and Celecoxib - Salimi, Ahmad; Neshat, Mohammad Reza; Naserzadeh, Parvaneh; Pourahmad, Jalal (Drug Research, 2019)
Nonsteroidal anti-inflammatory drugs (NSAIDs) like naproxen, diclofenac and celecoxib used to reduce pain. Many of these drugs have been associated with an increased risk of cardiovascular disease (CVD). The molecular mechanism(s) by which NSAIDs induce CVD up to now is unknown. We investigated the effects of naproxen, diclofenac and celecoxib with different structures and mechanism action on isolated rat heart mitochondria. All tested NSAIDs increased reactive oxygen species (ROS) formation, mitochondrial membrane collapse (MMP), mitochondrial swelling, lipid peroxidation, and glutathione and ATP depletion, which all of them play important roles in developing cardiotoxicity. We reported that mitochondrial permeability transition (MPT) pore sealing agents and antioxidants have the capacity to significantly prevent mitochondrial toxicity. Therefore, the inhibition of mitochondrial oxidative stress and mitochondrial dysfunction by MPT pore sealing agents and antioxidants can double confirm NSAID-induced cardiomyocytes toxicity is resulted from induction of apoptosis signaling trough ROS-mediated mitochondrial permeability transition.
Keywords: nonsteroidal anti-inflammatory drugs; mitochondria; naproxen; diclofenac; celecoxib; antioxidants